On e*_Singular Supplement Submodules - Kabban, Ali A.; Hasan, Wasan K. (Iraqi Journal of Science, 2025)
This paper aims present the main concepts of e*S-supplement submodules, weak e*S-supplement submodules, e*S-supplemented modules, weakly e*S-supplemented modules, cofinitely e*S-supplemented modules, and ⊕e*S-supplemented modules, as popularization of the concepts of supplement submodules, weakly supplement submodules, supplemented modules, weakly supplemented modules, cofinitely supplemented modules, and ⊕-supplemented modules respectively. We will prove some characteristics of these concepts.